Physical and social community characteristics associated with higher risk of diabetes-related hospitalization - Gupta, Neeru (My University, 2023)
Are the physical and social characteristics of our communities associated with being hospitalized for diabetes and commonly co-occurring health conditions, independently of one’s own risk factors? The researchers investigated this question by linking data from population health surveys, healthcare administrative sources, and geographical measures of community remoteness and socioeconomic marginalization.
Keywords: Health; Population & demography; Society & community